Rachunek kosztów klientów vs. rachunek kosztów działań - Kochalski, Cezary (Client Based Costing vs. Activity Based Costing, 2005)
Activity based costing conception is the subject of assessment in this paper. It has been proved that activity based costing sometimes can not be useful in achieving competitive advantage by company. In the context of value management, client based costing is recommended.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1060, s. 229-238